Physical and Chemical Properties of Cloud Droplet Residuals and Aerosol Particles During the Arctic Ocean 2018 Expedition - Karlsson, Linn; Baccarini, Andrea; Duplessis, Patrick; Baumgardner, Darrel; Brooks, Ian M.; Chang, Rachel Y.-W.; Dada, Lubna; Dällenbach, Kaspar R.; Heikkinen, Liine; Krejci, Radovan; Leaitch, W. Richard; Leck, Caroline; et al. (American Geophysical Union, 2022)
Detailed knowledge of the physical and chemical properties and sources of particles that form clouds is especially important in pristine areas like the Arctic, where particle concentrations are often low and observations are sparse. Here, we present in situ cloud and aerosol measurements from the central Arctic Ocean in August-September 2018 combined with air parcel source analysis. We provide direct experimental evidence that Aitken mode particles (particles with diameters less than or similar to 70 nm) significantly contribute to cloud condensation nuclei (CCN) or cloud droplet residuals, especially after the freeze-up of the sea ice in the transition toward fall. These Aitken mode particles were associated with air that spent more time over the pack ice, while size distributions dominated by accumulation mode particles (particles with diameters greater than or similar to 70 nm) showed a stronger contribution of oceanic air and slightly different source regions. This was accompanied by changes in the average chemical composition of the accumulation mode aerosol with an increased relative contribution of organic material toward fall. Addition of aerosol mass due to aqueous-phase chemistry during in-cloud processing was probably small over the pack ice given the fact that we observed very similar particle size distributions in both the whole-air and cloud droplet residual data. These aerosol-cloud interaction observations provide valuable insight into the origin and physical and chemical properties of CCN over the pristine central Arctic Ocean. ISSN:0148-0227 ISSN:2169-897X